Pre-service Teachers’ Dual Perspectives on Generative AI: Benefits, Challenges, and Integrating into Teaching and Learning - Bae, Haesol; Hur, Jaesung; Park, Jaesung; Choi, Gi Woong; Moon, Jewoong (Online Learning, 2024)
This study examined pre-service teachers’ perspectives on integrating generative AI (GenAI) tools into their own learning and teaching practices. Discussion posts from asynchronous online courses on ChatGPT were analyzed using the Diffusion of Innovations framework to explore familiarity, willingness to apply ChatGPT to instruction, potential benefits, challenges, and concerns about using GenAI in teaching and learning. The course discussions significantly increased pre-service teachers’ awareness and foundational knowledge while reducing anxiety towards AI technologies. However, despite exposure to ChatGPT, only a few confirmed intentions to adopt AI tools in their teaching practices, potentially reflecting lingering uncertainties evidenced by emotional responses, such as worry and concern. Professional development in AI literacy can address these uncertainties and enhance GenAI familiarity. The study offers insights into responsible GenAI adoption in education and how higher education can leverage ChatGPT to enhance pre-service teacher learning.